Molecular challenges of neuroendocrine tumors - Patel, Parthik (Oncol Lett, 2018)
Neuroendocrine tumors (NETs) are a very heterogeneous group that are thought to originate from the cells of the endocrine and nervous systems. These tumors develop in a number of organs, predominantly in the gastrointestinal and pulmonary systems. Clinical detection and diagnosis are reliable at the late stages when metastatic spread has occurred. However, traditional conventional therapies such as radiation and chemotherapy are not effective. In the majority of cases even surgical resection at that stage is unlikely to produce promising reusults. NETs present a serious clinical challenge, as the survival rates remain low, and as these rare tumors are very difficult to study, novel approaches and therapies are required. This review will highlight the important points of accumulated knowledge covering the molecular aspects of the role of neuroendocrine cells, hormonal peptides, the reasons for ectopic hormone production in NET, neuropeptides and epigenetic regulation as well as the other challenging questions that require further understanding.